Pandemic Ethics From COVID-19 to Disease X - Savulescu, Julian; Wilkinson, Dominic (Oxford University Press, 2023)
Pandemic ethics raises unresolved, fundamental, and controversial questions. The defining feature of a pandemic is its scale-the simultaneous threat to millions or even billions of lives. That scale creates and necessitates awful choices since the wellbeing and lives of all cannot be protected. Central to decisions are questions of the value of life, but also core human rights doctrines including the right to health, individual freedom and autonomy. Whether allocating limited supplies of ventilators, novel treatments, and vaccines or making policies that restrict movement and freedom, which values are most important? How should risk and burden be distributed? Should society save the greatest number of lives or accept higher deaths for the sake of other ethical values? These questions touched the lives of billions during the COVID pandemic. However, children who were home-schooled during the coronavirus outbreak will almost certainly face another pandemic in their lifetime - one at least as bad, and potentially much worse than this one. In this volume, bioethicists Dominic Wilkinson and Julian Savulescu have gathered leading philosophers, lawyers, economists, and bioethicists to address the global response to the pandemic, questions of liberty, how to balance competing ethical values and considerations of equality and inequality. The book critically reviews the COVID-19 pandemic to identify key lessons for "Disease X", the currently unknown but serious global threat that lies ahead.